3D Board Mania discover the world of radical skateboarding - Starke, John; Rhodes - Schofield, Martin; Starke, John (England Red Bird press, 2005)
Follow the ..... to watch the world's most extreme boardriders. Use your fantastic 3D specs to see them perform incredible tricks. With top tips and great pictures this book is the ultimate extreme boarding experience!
The World Around Us (Transportations)
Keywords: Transportation